PENGEMBANGAN PEMBELAJARAN BERBASIS E-LEARNING DENGAN APLIKASI MOODLE BERDASARKAN TEORI KONSTRUKTIVISTIK PADA MATERI MENGANALISIS PELUANG USAHA KELAS XI SMK - Safitri, Nelly; Murbojono, Rahmat; Syamsurizal, Syamsurizal (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
The development based learning e-learning with Moodle application based on the theory constructivist materials analyzing business opportunities XI class SMK is motivated by the limitations of the use of ICT in the learning process and the need for entrepreneurial learning media attractive and easy to use which can improve student learning outcomes. This study aims to (1) Develop e-learning courses with Moodle applications to support learning, develop learning with vocational e-learning materials based on the constructivist theory to analyze business opportunities and (2) Produce a product that has the attractiveness and easy to use. This type of research is the Research and Development using the model of Lee and Owens (2004), through several stages, namely: (1) analysis, (2) design,(3) development, (4) implementation, (5) evaluation. From the results of the development are as follows. (1) the development of e-learning with Moodle application based on the constructivist theory of matter to analyze business opportunities and well worthy to be used in class XI SMK 1 Kuala Tungkal and (2) produce e-learning has the attractiveness, and ease to use in learning activities. Feasibility of the e-learning based on expert validation studies that assess the field of e-learning include both categories, media design expert validation categorized as good, expert validation of multimedia including both categories. And experiments performed on the users (students) includes a small group of test activities, to perform pretest and posttest for the 15 students of SMK 1 Kuala Tungkal class XI Multimedia B, the result is the average value of the pretest 56.67 and posttest generate average value average 91.00. These results indicate that the developed e-learning effectively to improve student learning outcomes. Entrepreneurship For teachers, e-learning can be used in the learning process, so that the learning process will be more interesting and varied. The utilization of e-learning for the student as one of the active and independent learning resources. To promote the development of e-learning more should be tested also in larger groups and learning materials on the other. Keyword: E-learning, Moodle, Konsruktivistik and Business Opportunities